Assessing methane emission from dairy cows - Lingen, Henk J. van (Wageningen University, 2017)
A meta-analysis was performed to quantify relationships between enteric CH4 yield (per unit of feed and unit of milk) and milk FA profile in dairy cattle and to develop equations to predict CH4 yield based on milk FA profile of cows fed a wide variety of diets. Various milk FA concentrations were significantly or tended to be positively or negatively related to CH4 yield per unit of feed or milk. Mixed model multiple regression resulted in various milk FA included in optimal equations to predict CH4 yield per unit of feed and per unit of milk. These regression equations indicated a moderate potential for using milk FA profile to predict CH4 yield.